Triceps Tenotomy and Double Plate Stabilization of “Y-T” Fracture of the Humeral Condyle in Three Dogs - Sturgeon, C.; Wilson, A. M.; McGuigan, P.; Muir, P.; Lawes, T. J. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
Caudal elbow arthrotomy by use of triceps tenotomy was performed for open reduction of “Y-T” fractures of the humeral condyle in three dogs. Stabilization of the fracture was achieved by use of a bone screw inserted with a lag effect to compress the articular fracture and placement of bone plates on the caudolateral surface of the lateral epicondylar crest and the caudomedial surface of the medial epicondylar crest. This construct successfully maintained reduction in all three dogs without implant loosening or breakage. All three of the fractures healed satisfactorily without any evidence of progressive osteoarthritis. Long-term (median - 20 months) function of the affected limb was comparable to the contralateral limb, with little loss of elbow range-of-motion and minimal to an absence of lameness.Triceps tenotomy was used for open reduction of “Y-T” fractures of the humeral condyle in three dogs. Stabilization of the fracture with a bone screw inserted for lag effect and use of a bone plate on each epicondylar crest resulted in satisfactory healing of the fracture and good limb function in all of the patients.
Keywords: Triceps tenotomy; plate fixation; “Y-T” fracture; dog